The Effect Of Fear Of Missing Out Behavior On Social Media Fatigue Among Generation Z In Padang - Oktaviandra, Agung Izfa; Lestari, Yayuk; Diego, Diego; Elian, Novi (Journal of Education on Social Science (JESS), 2025)
The development of digital technology has made it easier for humans to communicate and access information, especially through social media, which has become an integral part of Generation Z's lives. The high intensity of social media use exposes Generation Z to the phenomenon of Fear of Missing Out (FoMO), which is the fear of being left behind in terms of information, trends, and social activities shared by others. This condition has the potential to cause social media fatigue, which is a feeling of tiredness, boredom, and overwhelm due to an excessive flow of information. The aim of this study is to analyze the influence of FoMO on social media fatigue among Generation Z in Padang. Using purposive sampling, this study involved 100 respondents. In this study, the respondents were Generation Z active social media users in Padang City who were between the ages of 18 and 28. The test was conducted using simple linear regression analysis. The results of the study show that there is a relationship between FoMO and social media fatigue with a value of 34.3%. The results of this study are expected to contribute theoretically to communication studies and practically to efforts to improve the digital literacy of young people so that they can use social media more wisely.